Design and Cytotoxicity Evaluation of a Cancer-targeting Immunotoxin Based on a Camelid Nanobody-PE Fusion Protein - Khoshbakht, Mona; Forghanifard, Mohammad Mahdi; Aghamollaei, Hossein; Amani, Jafar (Iranian journal of immunology, 2024)
Developing effective targeted treatment approaches to overcome drug resistance remains a crucial goal in cancer research. Immunotoxins have dual functionality in cancer detection and targeted therapy. This study aimed to engineer a recombinant chimeric fusion protein by combining a nanobody-targeting domain with an exotoxin effector domain. The chimeric protein was designed to bind surface-expressed GRP78 on cancer cells, facilitating internalization and inducing apoptosis to inhibit proliferation and survival. Using a flexible linker, we designed two constructs linking VHH nanobody domains to Pseudomonas exotoxin (PE) domains II, III, and Ib. These constructs were then optimized for expression in E. coli BL21 (DE3) using the pET28a vector. Following the expression of the recombinant proteins, we purified them and tested their binding capability, cytotoxicity, and ability to induce apoptosis in breast cancer cell lines MDA-MB-231 and MCF-7, as well as in control cell lines HEK-293 and MDA-MB-468. The binding affinity was measured using a cell-based ELISA, internalization was assessed through Western blotting, cytotoxicity was evaluated by an MTT assay, and apoptosis was determined using flow cytometry with an Annexin V kit. The immunotoxin specifically bound to cancer cells expressing csGRP78. The results of the cytotoxicity test showed that the cytotoxic effect of two constructs, I and II, depended on concentration and time. With an increase in both components, the effect of recombinant proteins also increased. Both constructs were able to penetrate and induce apoptosis in csGRP78+ cells. These immunotoxin structures showed therapeutic potential against GRP78-expressing cancers, making them suitable candidates for targeted therapy pending in vivo studies.